2016
DOI: 10.1080/15504263.2016.1175262
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Recovery Housing: Prioritizing Choice in Homeless Services

Abstract: Housing options for people exiting homelessness and seeking recovery from substance use disorders are limited. Policies tend to favor low-demand models such as housing first and permanent supportive housing that do not require abstinence, but offer immediate housing placement based on consumer choice and separate housing from clinical services. While these models have proven effective in promoting housing retention, especially among individuals with a primary diagnosis of mental illness, evidence to support po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
(73 reference statements)
2
15
0
Order By: Relevance
“…Moreover, both housing status and housing stability predicted a variety of problem areas controlling for demographic factors. These findings support the growing contention in the broader literature on homelessness that consumer perceptions about housing choices should be considered when providing housing assistance (Paquette & Pannella Winn, 2016; Pannella Winn & Paquette, 2016). …”
Section: Discussionsupporting
confidence: 79%
“…Moreover, both housing status and housing stability predicted a variety of problem areas controlling for demographic factors. These findings support the growing contention in the broader literature on homelessness that consumer perceptions about housing choices should be considered when providing housing assistance (Paquette & Pannella Winn, 2016; Pannella Winn & Paquette, 2016). …”
Section: Discussionsupporting
confidence: 79%
“…The study findings reported here support recommendations made by Paquette and Winn, 17,18 who suggest a better approach to co-occurring problems of substance abuse problems among persons who are homeless or unstably housed would be to provide funding for a broader based system of choices that includes HF, SLHs, and other housing options. The availability of these distinct housing options would provide greater responsivity to individuals.…”
Section: Future Directionssupporting
confidence: 82%
“…It has been argued that a significant limitation in current homeless services is the failure to fund different housing options that would present choices to consumers. 17,18 While the U.S. Department of Housing and Urban Development provides funding or some types of housing programs (e.g., HF), it does not provide funds for others (e.g., SLHs and other types of recovery residences).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The article by Paquette and Winn (2016) summarizes system-level barriers to integrating recovery housing (i.e., abstinence-based living environments that promote recovery from addiction) and homelessness services. They highlight key differences between recovery housing, which presumes abstinence, and “housing first” approaches, in which neither abstinence nor service use is a precondition to housing, and offer recommendations for research, policy, and practice to better integrate recovery housing into homelessness service continuums.…”
mentioning
confidence: 99%